Applying SERVQUAL for Measuring Customer Satisfaction on Institute for Research and Community Service: A Case Studi at Universitas Muhammadiyah Surakarta - Hari Prasetyo; Atik Setiawati; Gusti Fauza (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
This study aims to design a valid instrument for measuring the satisfaction of internal and external users on service quality provided by an institute for research and community service (LPPM) at a university. The SERVQUAL model is applied and a case study was conducted at Universitas Muhammadiyah Surakarta. Twenty-eight research attributes and twenty attributes of community services have been developed to measure the LPPM service quality based on five dimensions criteria namely tangible, reliability, responsiveness, assurance, and empathy. The developed attributes were validated by experts, e.g., head of LPPM and his staff. Further, using bivariate Pearson correlation and Cronbach alpha those attributes were tested for validity and reliability using SPSS 23. The result showed that all attributes in the instrument were valid and reliable. Furthermore, based on the Actual SERVQUAL Score (ASC), all attributes have score more than 75%, which can be classified as better than “good” according to the UMS Quality Assurance Agency (LJM). It indicates that the customers are satisfied with the services. However, based on the service quality gap analysis (i.e., gap between the perceptions and expectations of users), all statements showed negative results, which means that the perception is lower than expectation. Hence, improvements are still required especially to those attributes with high gap